2016
DOI: 10.1007/s00038-016-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of health-care services among immigrants recruited through non-profit organizations in southern Italy

Abstract: This study yielded current and broader insight into the model of health-care utilization among immigrants. The findings adds to our understanding of the third-sector organizations' role in facilitating immigrants' access to services offered by the Italian National Health Service, contributing to the extensive discussion on how to best manage migrant health care in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In Southern Italy previously published data have focused their attention on investigating the health conditions, mainly the epidemiological characteristics of different diseases [ 11 13 ] and the patterns of access and utilization of healthcare services [ 14 ] by groups of immigrants. To date, there is relatively little work examining the occurrence of violence in these communities [ 7 , 15 18 ], despite the fact that this is a significant global public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Italy previously published data have focused their attention on investigating the health conditions, mainly the epidemiological characteristics of different diseases [ 11 13 ] and the patterns of access and utilization of healthcare services [ 14 ] by groups of immigrants. To date, there is relatively little work examining the occurrence of violence in these communities [ 7 , 15 18 ], despite the fact that this is a significant global public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed in Pavia has shown that only half (49.7%) of the sample of migrant women receive a diagnostic procedures and/or drug prescription and only a third had a preventive intervention or chronic disease control [ 64 ]. There is a clear need to understand and implement new strategies to access and remove barriers to care concerning the model of health-care utilization among immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, foreigners tend to overuse emergency departments where access appear easier and more immediate [23,24]. This situation unavoidably leads to an increase in healthcare costs for the inappropriate use of emergency departments and to a widening of health inequalities due to a lack of prevention and management of chronic diseases, that are estimated to affect four foreigners out of ten in Italy [25,26]. According to our results, foreigners show more behavioural risk factors for NCDs: smoking, sedentary lifestyle and lower intake of fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%